On the asymptotic behavior of sequences given by recursion relations in a Banach space - Tomilov, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
The criteria of boundedness and asymptotic periodicity are obtained for certain recursion sequences in a Banach space.